Different behaviour of NOX2 activation in patients with paroxysmal/persistent or permanent atrial fibrillation. Issue 14 (23rd May 2012) - Cangemi, Roberto; Celestini, Andrea; Calvieri, Camilla; Carnevale, Roberto; Pastori, Daniele; Nocella, Cristina; Vicario, Tommasa; Pignatelli, Pasquale; Violi, Francesco
Abstract : Background: NOX2, the catalytic subunit of NADPH oxidase, is suggested to play a role in favouring the occurrence of atrial fibrillation (AF) after cardiac surgery via formation of reactive oxidant species. However, its role in spontaneous AF is still unclear. Objective: To define the role of NOX2 and isoprostanes, a marker of oxidative stress, in the different settings of AF. Methods: The study was performed on 174 patients with AF (82 with paroxysmal/persistent AF and 92 with permanent AF) and 90 controls matched for sex, age and atherosclerotic risk factors. Urinary isoprostanes and serum levels of soluble NOX2-derived peptide (sNOX2-dp) were measured in each patient. Results: Urinary isoprostanes and sNOX2-dp concentrations were significantly higher in patients with paroxysmal/persistent AF than in those with permanent AF and controls. Compared with controls, patients with permanent AF showed a weak increase in sNOX2-dp and no difference in isoprostanes. Multivariable analyses demonstrated that baseline values of sNOX2-dp and urinary isoprostanes were independently associated with the type of AF (paroxysmal/persistent vs permanent; β=−224, p=0.007 and β=−231, p=0.005, respectively). A significant correlation between sNOX2-dp levels and urinary excretion of isoprostanes was also detected (R=0.707, p<0.001). Conclusions: This study provides evidence that NOX2 is upregulated only in patients with paroxysmal/persistent AF and is responsible for overproduction of isoprostanes. This finding warrants further study to see if inhibition of NOX2 may reduce the risk of paroxysmal/persistent AF.